Incidence and mortality from colon and rectal cancer in Midwestern Brazil - Anderson Gomes de Oliveira; Maria Paula Curado; Alice Koechlin; José Carlos de Oliveira; Diego Rodrigues Mendonça e Silva
ABSTRACT: Objective: To describe the incidence and mortality rates from colon and rectal cancer in Midwestern Brazil. Methods: Data for the incidence rates were obtained from the Population-Based Cancer Registry (PBCR) according to the available period. Mortality data were obtained from the Mortality Information System (SIM) for the period between 1996 and 2008. Incidence and mortality rates were calculated by gender and age groups. Mortality trends were analyzed by the Joinpoint software. The age-period-cohort effects were calculated by the R software. Results: The incidence rates for colon cancer vary from 4.49 to 23.19/100,000, while mortality rates vary from 2.85 to 14.54/100,000. For rectal cancer, the incidence rates range from 1.25 to 11.18/100,000 and mortality rates range between 0.30 and 7.90/100,000. Colon cancer mortality trends showed an increase among males in Cuiabá, Campo Grande, and Goiania. For those aged under 50 years, the increased rate was 13.2% in Campo Grande. For those aged over 50 years, there was a significant increase in the mortality in all capitals. In Goiânia, rectal cancer mortality in males increased 7.3%. For females below 50 years of age in the city of Brasilia, there was an increase of 8.7%, while females over 50 years of age in Cuiaba showed an increase of 10%. Conclusion: There is limited data available on the incidence of colon and rectal cancer for the Midwest region of Brazil. Colon cancer mortality has generally increased for both genders, but similar data were not verified for rectal cancer. The findings presented herein demonstrate the necessity for organized screening programs for colon and rectal cancer in Midwestern Brazil.